Analisis Kesulitan Belajar Siswa dalam Menyelesaikan Soal Matriks - Dwitifani Hermanto, Berliani; Susilawati, Susilawati (AB-JME: Al-Bahjah Journal of Mathematics Education, 2023)
Learning difficulties are a disorder of conditions in students that deviate between their abilities and achievements aimed at three basic academics such as reading, writing, and calculating. This study aims to identify and describe the difficulty of learning mathematics in matrix material. This study used qualitative research methods. The subjects of this study were students of class XI SMAIQu Al-Bahjah. Data collection techniques using observation, tests, and interviews. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study indicate that students experience difficulties in solving matrix problems on indicators of lack of understanding of concepts, miscalculations and errors in the use of symbols. The percentage of students' lack of understanding is 65%, the percentage of calculation errors is 30% and the percentage of errors in symbol use is 5%. The most difficulty made by students is the lack of understanding of the concept. One of the causes of the lack of understanding of the concept is because students do not understand the concept of material related to the matrix so that students have difficulty solving problems.